2011
DOI: 10.1186/1471-2334-11-158
|View full text |Cite
|
Sign up to set email alerts
|

Trends in chlamydia and gonorrhea positivity among heterosexual men and men who have sex with men attending a large urban sexual health service in Australia, 2002-2009

Abstract: BackgroundTo determine whether chlamydia positivity among heterosexual men (MSW) and chlamydia and gonorrhea positivity among men who have sex with men (MSM), are changing.MethodsComputerized records for men attending a large sexual health clinic between 2002 and 2009 were analyzed. Chlamydia and gonorrhea positivity were calculated and logistic regression used to assess changes over time.Results17769 MSW and 8328 MSM tested for chlamydia and 7133 MSM tested for gonorrhea. In MSW, 7.37% (95% CI: 6.99-7.77) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…The recent increase in new diagnoses of sexually transmitted HIV infections compared with the decrease in transmission by the use of injected drugs [26] along with the low frequency of condom use, highlights the persistence of high-risk sexual behaviours in the general Spanish population, as well as in other countries such as Australia [27][28][29]. Our study supports this observation in a particular subset of the Spanish population living in the capital of Spain.…”
Section: Discussionsupporting
confidence: 78%
“…The recent increase in new diagnoses of sexually transmitted HIV infections compared with the decrease in transmission by the use of injected drugs [26] along with the low frequency of condom use, highlights the persistence of high-risk sexual behaviours in the general Spanish population, as well as in other countries such as Australia [27][28][29]. Our study supports this observation in a particular subset of the Spanish population living in the capital of Spain.…”
Section: Discussionsupporting
confidence: 78%
“…Genital symptom data are currently not collected as part of the ACCESS study. However, previous reports from one large ACCESS sexual health service showed that 55.9% of heterosexual men18 and 42% women4 were either symptomatic presentations or contacts of people with infection. Trends in more symptomatic sexually transmitted infections (such as syphilis and gonorrhoea) reported from sexual health services have better reflected population-based notifications 19 20.…”
Section: Discussionmentioning
confidence: 92%
“…We consider these possibilities to be unlikely for a number of reasons including the similarity between our earlier findings to the end of 20081 and the findings of the Australia-wide surveillance programme,2 the fact that our data have been adjusted for sexual behaviour which is the most important predictor of GW, the very large effect size that we have demonstrated and finally the absence of a decline in GW in unvaccinated groups in any risk group before July 2007. In addition, previous work has shown an increasing prevalence of other sexually transmitted infections among heterosexuals attending MSHC, which would make a fall in GW without vaccination even more unlikely10 11…”
Section: Discussionmentioning
confidence: 99%